Does Dexmedetomidine Protect the Visceral Organs against the Asphxia - Ayse Mizrak (International Journal of Veterinary Science and Research - Peertechz Publications, 2019)
Background: This study was conducted to determine whether dexmedetomidine exhibits a protective effect against sudden and short term hypoxia on brain, heart, lung, liver, and kidney in rat model which sudden hyperglycemia and hypertension developed. Methods: In this randomised and double blind study, the experiment was performed on 30 male Wistar Albino rats 250-300 g weight. The rats were randomly assigned into 2 groups which are control group (C, n = 15), and dexmedetomidine group (D, n = 15). All rats were made hyperglycemic by a single injection of streptozotocin (STZ) (50 mg/kg) then, adrenalin (0.03 mg/kg) was injected intraperitonealy to make sudden hypertension. Dexmedetomidine (10 µg/kg/min, total dose 2.5-3.3 µg) was infused intraperitonealy in group D, and saline to group C. They were sacrified until observing siyanosis on the feet and stopping the body movement.  Results: The incidence of liver's congession (p=0.01) and the incidence of schistocytes (p=0.4) in group C were significantly higher than in group D. The grade of congession in group C was significantly higher than in group D (p=0.004). In group C, the mean arterial blood pressure (MAP) (p= 0.0001), heart rate (HR) (p= 0.004), and the blood glucose (p= 0.0001) values after-experiments period were significantly higher than the values before-experiments period.  Conclusions: Dexmedetomidine 10 µg/kg/min could protect the liver against the congession and lung against the severe congession but could not protect the brain, heart and kidney in hyperglycemic and hypertensive rat model.